Selective regulation of type II interferon‐inducible genes by NPM1/nucleophosmin. Issue 2 (1st January 2018) - Abe, Mayumi; Lin, Jianhuang; Nagata, Kyosuke; Okuwaki, Mitsuru
Abstract : Nucleophosmin (NPM1) is a multifunctional nucleolar protein. Here, we analyze the role of NPM1 in gene expression using our previous microarray data and find a relationship between NPM1 and interferon (IFN)‐γ‐inducible genes. We show that NPM1 selectively regulates the expression of a subset of IFN‐γ‐inducible genes and directly binds to two important transcription factors in the type II IFN pathway: signal transducer and activator of transcription 1 and interferon regulatory factor 1 (IRF1). Furthermore, NPM1 is found to regulate the IFN‐γ‐inducible promoter activity of major histocompatibility complex class II transactivator (CIITA), and mutation of the IRF1‐binding site on the CIITA promoter abolishes the effect of NPM1. Our results suggest a novel mechanism for IFN‐γ‐mediated gene expression by NPM1. Abstract :